2012
DOI: 10.2174/092986712803988929
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Toxicity and Hepatic Oxidative Stress

Abstract: Cocaine belongs to the group of psychostimulants and together with amphetamines has been recognized as one of the most significant examples of drug abuse. Cocaine abuse is due to intense feelings of euphoria, friendliness, empathy, and hyperactivity, which result from its potent inhibitory effects on presynaptic dopamine and noradrenaline re-uptake. Misuse of cocaine can induce severe toxic effects, including neurotoxicity, cardiotoxicity, hepatotoxicity. There are a number of data, both experimental and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
2
17
0
2
Order By: Relevance
“…Furthermore, several lines of evidence indicate that excessive OS with increased free radical generation, impairment of mitochondrial respiration, and intense inflammatory reaction plays a crucial role in cocaine-induced hepatotoxicity. OS is associated with the dysregulation of signaling pathways modulating cell death and survival, which leads to necrosis and apoptosis of hepatocytes [ 6 ]. Although previous studies have yielded mechanistic information on cocaine-induced hepatotoxicity, the current understanding on this toxic event remains insufficient [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several lines of evidence indicate that excessive OS with increased free radical generation, impairment of mitochondrial respiration, and intense inflammatory reaction plays a crucial role in cocaine-induced hepatotoxicity. OS is associated with the dysregulation of signaling pathways modulating cell death and survival, which leads to necrosis and apoptosis of hepatocytes [ 6 ]. Although previous studies have yielded mechanistic information on cocaine-induced hepatotoxicity, the current understanding on this toxic event remains insufficient [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well described that the prevention of OS generation might have therapeutic advantages in several diseases [ 6 , 10 , 11 ]; therefore, the investigation of putative new compounds with antioxidant properties might be promising. The herb Cannabis sativa (“marijuana,” “hemp”) has been known for centuries due to its abuse-related effects and possible therapeutic uses, including the treatment of inflammation, diabetes, cancer, affective or neurodegenerative diseases, and epilepsy-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MDMA (ecstasy) and cocaine can cause chronic hepatitis and liver fibrosis (Payance, Scotto, Perarnau, de Muret, & Bacq, 2013). In addition, cocaine use can induce severe hepatotoxicity (Vitcheva, 2012) and cannabis use exacerbates HCV-associated liver disease (Hezode et al, 2005; Ishida et al, 2008). However, few studies to date have reported the use of addictive drugs in people with HIV-HCV co-infection relative to persons with HIV mono-infection.…”
Section: Introductionmentioning
confidence: 99%
“…Está descrito que en la hepatotoxicidad por cocaína, la peroxidación de lípidos inducida por estrés oxidativo se encuentra relacionada con las hormonas sexuales, especialmente la testosterona, con menor daño en mujeres con ovarios intactos 19,20 . Sin embargo, nuestros hallazgos se contraponen a estas observaciones, probablemente debido al menor número de mujeres, por lo que no podemos aseverar que esté relacionado con el efecto de hormonas sexuales como ha sido descrito para otras alteraciones.…”
Section: Discussionunclassified